Sistem Informasi Kependudukan Kecamatan Singkut - reza saputra, Fharis; Eni Rohaini; Riza Pahlevi (LPPM Universitas Dinamika Bangsa, 2025)
Abstract−Singkut District faces problems in managing the creation of certificates (domicile, not married, not having a house, death, business domicile, and marriage introduction). The process is still manual using Microsoft Word, with files stored separately in many folders, making it difficult to find letters by category. Files are not integrated, causing data duplication and slowing down services. This results in residents having to wait a long time, queuing, and not being able to access service information online without coming directly to the administration section. The purpose of this study is to analyze the current system, in order to overcome the problems faced at the Singkut District Office, by designing a Web-Based Population Information System Design in Singkut District. The Research Framework that will be carried out in solving the problems discussed is, conducting identification, conducting information searches based on theoretical foundations, collecting data using observation and interview methods, analyzing to find solutions to the problems faced by the Singkut District Office. The system development method uses the agile development model, the implementation of this research uses the PHP Programming Language and MySQL DBMS. Until it produces a data processing application that is expected to facilitate data processing and report generation